Cajanolactone A, a Stilbenoid From Cajanus canjan (L.) Millsp, Prevents High-Fat Diet-Induced Obesity via Suppressing Energy Intake - Luo, Zhuohui; Huang, Jiawen; Li, Zhiping; Liu, Zhiwen; Fu, Linchun; Hu, Yingjie; Shen, Xiaoling (Frontiers in Pharmacology, 2021)
Cajanolactone A (CLA) is a stilbenoid isolated from Cajanus canjan (L.) Millsp with the potential to prevent postmenopausal obesity. In this study, the effect of CLA on high-fat diet (HFD) induced obesity in female C57BL/6 mice was investigated. It was found that, treatment with CLA reduced the energy intake and effectively protected the mice from HFD-induced body weight gain, fat accumulation within the adipose tissues and liver, and impairment in energy metabolism. Further investigation revealed that CLA significantly down-regulated the expression of ORX, ORXR2, pMCH and Gal in the hypothalamus and antagonized HFD-induced changes in the expression of UCP1, Pgc-1α, Tfam and Mfn1 in the inguinal white adipose tissue (iWAT); Caveolin-1, MT and UCP3 in the perigonadal white adipose tissue (pWAT); and Pdhb, IRS2, Mttp, Hadhb and Cpt1b in the liver. CLA also protected the pWAT and liver from HFD-induced mitochondrial damage. However, neither HFD nor CLA showed an effect on the mass of brown adipose tissue (BAT) or the expression of UCP1 in the BAT. In summary, our findings suggest that CLA is a potential drug candidate for preventing diet-induced obesity, at least in females. CLA works most likely by suppressing the hypothalamic expression of orexigenic genes, which leads to reduced energy intake, and subsequently, reduced fat accumulation, thereby protecting the adipose tissues and the liver from lipid-induced mitochondrial dysfunction.